Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1055/s-0040-1713728
|View full text |Cite
|
Sign up to set email alerts
|

Salvage of the Failed Total Wrist Arthroplasty: A Systematic Review

Abstract: Abstract Background Although the performance of total wrist arthroplasty systems has improved, failure is encountered and is a major challenge to manage. Questions Does physical function improve with surgical management of the failed wrist arthroplasty? Is there an improvement in secondary outcome measures including pain, grip strength, and range of motion? What are the reasons for failure in primary total wrist arthroplasty? What are the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(58 citation statements)
references
References 22 publications
0
41
1
6
Order By: Relevance
“…The rate of 12% of revision in our study remained lower than some rates reported for TWF and TWA. [31][32][33] Herzberg et al 34 reported, in his series of TWA using ReMotion 6% of revision.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The rate of 12% of revision in our study remained lower than some rates reported for TWF and TWA. [31][32][33] Herzberg et al 34 reported, in his series of TWA using ReMotion 6% of revision.…”
Section: Discussionmentioning
confidence: 98%
“…These secondary procedures did not affect the final results and no significant difference in final outcomes was found between the patients requiring surgical revision and the other patients (►Table 7). Berber et al, 33 in a systematic review of 214 revision procedures for TWA failure, found a temporary improvement in functional scores at 1 year, which deteriorated at 5 years with a high rate of rerevision regardless of the type of revision (21% after TWF and 35% after TWA).…”
Section: Discussionmentioning
confidence: 99%
“…► artrodesis de muñeca ► fusión de muñeca ► placa ► tasa de consolidación ► complicaciones recent systematic review (2018) found a complication rate of 6.1% for total wrist arthrodesis. 14 In this context, a low profile and variable angle locked plate (TriLock APTUS 2.5 wrist arthrodesis plate, Medartis AG, Basel, Switzerland) was developed for total wrist arthrodesis. It has rounded edges and an anatomically curved "low profile" minimizing the potential for soft tissue irritation or tendon friction.…”
Section: Palabras Clavementioning
confidence: 99%
“…11-13 Una revisión sistemática más reciente (2018) encontró una tasa de complicaciones del 6,1% para la artrodesis total de muñeca. 14 En este contexto, se desarrolló una placa bloqueada de bajo perfil y ángulo variable (placa de artrodesis de muñeca TriLock APTUS 2.5, Medartis AG, Basilea, Suiza) para la artrodesis total de muñeca. Tiene bordes redondeados y un "perfil bajo" anatómicamente curvado que minimiza la posibilidad de irritación de los tejidos blandos o fricción de los tendones.…”
Section: Introductionunclassified
“…In this context, studies have reported better results with the fourth generation of artificial wrist joints ( Bidwai et al, 2013 ; Froschauer et al, 2021 ). In contrast to wrist fusion, TWA preserves wrist mobility and provides effective pain relief ( Fischer et al, 2020 ; Berber et al, 2020 ; Matsui et al, 2020 ; Zhu et al, 2021 ). However, the carpal component still tends to loosen on long-term follow-up ( Reigstad et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%